The influence of political connection on corporate social responsibility: Evidence from listed private companies in China - Huang Haifeng; Zhenrui Zhao (International Journal of Corporate Social Responsibility (JCSR), 2016)
In recent years, Chinese private companies have improved a lot in corporate social responsibility (CSR) performance, especially in the philanthropic area. However, private companies' awareness and performance of social responsibility still have a big disparity with SOEs. And private companies' policy of social responsibility is subjective and preferential. To explain this contradiction, this paper tries to introduce political connection and, based on stakeholder salience theory, to test how political connection changes managers' perception of stakeholders' relative importance and cause changes in stakeholders' satisfaction level of social responsibility requirement. The result shows that (1) political connection has positive influence on private companies' CSR; (2) companies with political connection are significantly better than the ones without political connection in society-oriented and customers-oriented responsibility; (3) two kinds of companies have no significant difference in investors-oriented responsibility; (4) as for government-oriented and employee-oriented responsibility, companies with political connection are worse than ones without political connection. These findings are significant for China's future construction of competition system and private companies' choice of stakeholders and future investment.
Keywords: 650; Political connection; Corporate social responsibility; Stakeholder salience theory